Sistem Deteksi Bentuk Kecacatan Benda Padat Menggunakan Teknik Variasi Sudut Ultrasonik - Taufiq Nur Syahril Sidiq; Abdul Rouf; Tri Wahyu Supardi (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
Making solid material frequent problems of internal defect. This research intends to make a system to detect the form of defect in solid materials using ultrasonic waves. Components that was used in the system is a generator function, an op-amp, ultrasonic sensor, oscilloscope and cylindrical solid material The method that used is reflected method of ultrasonic. Ultrasonic waves emitted from the transmitter to a solid material and the receiver will read a results of the reflection that occurs due to differences in medium objects. Oscilloscope will read of ultrasonic. Recitation will be done to determine the form of any cylindrical solid object.The trial system by a unit transmitter emits ultrasonic waves on the side solid material. A solid body rotated every multiple 20˚ of 0-180˚ to get an angle variations. The result obtained that waves as 40 khz can detect the form of solid material defect. The form of defect in a solid material has different wave pattern. Constant wave patterns with small amplitudo is a cylindrical material without defect, constant wave patterns with more much amplitudo is cylindrical material with cylindrical defect also and wave patterns whose amplitudo is different in any variation angle is cylindrical solid with cubicaly defect.